METHODOLOGY FOR INVESTIGATING THE PROBABILITY-TIME CHARACTERISTICS OF NETWORK ATTACKS IN THE SIMULATION MODELLING SOFTWARE ENVIRONMENT - Irina G. Drovnikova; Anatoly A. Zmeev; Anton D. Popov; Evgenii A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Abstract. Objectives An analysis of open access literature sources and normative documents on the problem of information protection in automated systems was carried out. This showed the absence in these documents of quantitative parameters of the probability-time characteristics of network attacks carried out on information resource of automated systems. To such parameters one can attribute the average time of a network attack in one of its states, realising destructive impacts, in order to develop an effective model for countering threats implemented in systems and information security products. Methods One of the methods for solving this problem is a full-scale experiment; however, in practice many difficulties arise during its implementation, namely the determination of the probabilitytime characteristics of network attacks (if the time is much less than a second). To solve this complex problem, it is necessary to use new information technologies, which include the CPNTools simulation modelling software environment. Results The methodology for determining the probability-time characteristics of network attacks carried out on the information resource of automated systems (the quantitative values of the times of the network attack at all states of the formal model of their operation) is developed. A classification of network threats comprising unauthorised access in automated systems based on the data bank of the Federal Service for Technical and Export Control of Russian Federation is proposed. Conclusion  The output data of the methodology developed in the article are the probability-time characteristics of network attacks carried out on the information resource of automated systems. This data was obtained during the simulation using CPNTools software environment in the form of the residence time (realisation) in one of the realisation states of these destructive effects in automated systems. The main aspects of the obtained results are analysed and prospects for their future use, connected with the increase of real security of existing, as well as developed, automated systems, are outlined.